Lei das Agências : An Analysis of Draft Law on Regulatory Agencies - World Bank Group (World Bank, Washington, DC, 2017)
Since 2013, a new legislation was being drafted by the Senate of Brazil, in response to the perception that the Agencies often lack financial, administrative and decision making autonomy, are subject to capture by both overt and tacit political interference, with appointees lacking the necessary skills and independence. In infrastructure, regulatory uncertainty and the resort to the court of law in matters that should normally be decided by the agencies and accepted by affected parties is particularly harmful when government faces excess (and growing) demand for infrastructure services. After being discussed and approved in two key Senate commissions, the draft law (DL) was approved unanimously by the Senate Special Commission on National Development with no need to go to the floor. The DL provides the agencies with considerable formal autonomy, being no coincidence that this is made explicit at the outset of the legislation (Article 3). While the DL provides substantial autonomy to the agencies, it also defines the mechanisms for external control and accountability in its second chapter. The fundamental reason for the support of the DL is the high degree of autonomy conferred on the agencies, guaranteeing independence of political interests, technical excellence, and greater transparency and accountability. Finally, the DL strongly encourages inter-agency cooperation, partly in response to a recurrent criticism regarding barriers facing firms when dealing with different government agencies both national and subnational.